The effect of traumatic dental occlusion on the degradation of periodontal bone in rats - Brandini, Daniela Atili [UNESP]; Amaral, Marina Fuzette [UNESP]; Poi, Wilson Roberto [UNESP]; Casatti, Cláudio Aparecido [UNESP]; Bronckers, Antonius Ljj; Everts, Vincent; Beneti, Igor Mariotto [UNESP] (Wolters Kluwer, 2016)
Context: A better understanding of the relation between traumatic dental occlusion and periodontal changes is needed. Aims: This study aimed to evaluate the pattern of osteoclastic activity in the periodontal bone in front of the traumatic dental occlusion in rat molars. Patients and Methods: Traumatic dental occlusion (TO) was induced in twenty rats, which were sacrificed after periods of 2, 5, 7, and 14 days. Transversal histological sections of both jaws were stained with tartrate-resistant acid phosphatase and hematoxylin and eosin. Mann-Whitney U-Test was used for group comparison, and Pearson's correlation test was applied for the number of osteoclasts and bone area (BA). Results: Traumatic dental occlusion caused an increase in the number of osteoclasts in the bone of the upper and lower right first molar from days 2-5 to 2-14, respectively. In the TO groups, the number of osteoclasts on the lamina dura and in the center of the alveolar bone septum, respectively, increased almost 4-fold and 9-fold in the lower jaw; and 3-fold and 5-fold in the upper jaw, during all periods. In the TO groups, the BA of the alveolar bone septum was substantially reduced. There was a negative correlation between the number of osteoclasts and BA in both jaws during all experimental periods. Conclusions: Traumatic dental occlusion increases osteoclast activity in the alveolar lamina dura and in the center of alveolar bone and stimulates a higher degradation in the center of the alveolar bone septum.
Keywords: Alveolar bone; dental occlusion; osteoclasts; periodontium; traumatic